Aprendizaje basado en problemas y su relación con el proceso de enseñanza-aprendizaje de las matemáticas en la Unidad Educativa Federación Deportiva de Cotopaxi, cantón La Mana, periodo 2023- 2024. - Changoluisa Toaquiza , Wilmer Javier (2024)
The present research objective was: To analyze Problem-Based Learning (PBL) and its relationship in the teaching-learning process of the students of the Educational Unit "Sports Federation of Cotopaxi" Canton La Manà; perìodo 2023-2024, which will allow the improvement of mathematics learning, the type of applied research was descriptive with a qualitative approach. Methods such as inductive and deductive were used, in order to guarantee a broad knowledge of the object of research, the technique used was an interview with the director and a survey addressed to teachers and students, The information was collected to later carry out the analysis and interpretation, which were evidenced in the following results: The surveyed student population states that they are unaware of the problem-based learning strategy, , In addition, they express that their low academic performance is affected by the limited application of innovative didactic strategies and they agree that the teacher should apply mathematics classes to improve the teaching-learning process. What has been expressed by the teachers ratifies the impact on student performance in mathematics, they also consider it necessary to apply it to improve their teaching process and believe that it is ideal for the acquisition of knowledge, skills, abilities, and attitudes in students through real-life situations. Finally, with the results found in the evaluation, it was proposed to carry out a teacher training plan on Problem-Based Learning in mathematics